Pediatric Malignant Ovarian Tumors: 15 Years of Experience at a Single Institution - Say-Tin Yeap; Chih-Chen Hsiao; Chih-Sung Hsieh; Hong-Ren Yu; Yu-Chieh Chen; Jiin-Haur Chuang; Jiunn-Ming Sheen (Pediatrics and Neonatology)
Malignant ovarian tumors in children are relatively rare. We reviewed our 15-year experience to understand their clinical presentations, managements, and prognoses. Methods: There were 15 children who were diagnosed to have malignant ovarian tumors from January 1994 to June 2009 in our hospital. The presenting symptoms, treatments, and outcomes were obtained retrospectively from the medical records. Results: The median age at presentation was 13 years. The most common presenting symptom was abdominal pain, occurring in 10 patients (66.7%). The tumors were in the left side in 10 patients (66.7%). The pathologic diagnoses were yolk sac tumors in four patients, immature teratomas in four, dysgerminomas in three, malignant mixed germ cell tumors in three, and carcinosarcoma in one patient. According to the Federation Internationale de Gynecologie Oncologique classification, seven girls had Stage I, one had Stage II, and seven had Stage III disease. Thirteen patients received chemotherapy with platinum-based regimens. Three patients died of their disease: one of yolk sac tumor, one of malignant mixed germ cell tumor, and one of carcinosarcoma. They all had Stage III disease at diagnosis. The 10-year overall survival and disease-free survival rates were 77% and 69%, respectively. Conclusions: Pediatric malignant ovarian tumors were highly curable disease if they were not in the advanced stage at presentation. Earlier consideration of malignant ovarian tumor in the differential diagnosis of young girls with abdominal pain is important.